Model Pengembangan Usaha Mikro Industri Pakaian Jadi (Konveksi) Pada Era Pandemic Disease (Covid-19) Di Kota Bukittinggi dalam Perspektif Ekonomi Syariah - Sinky Adella; Rusyaida Rusyaida; Khalila Husna Sari; Oktri Lola Sari; Anwar Sholihin (ITB AAS INDONESIA Surakarta, 2022)
The Covid-19 pandemic has an impact not only on the health aspect but also on the business aspect. To prevent the spread of Covid-19, the government issued a policy of limiting community activities that impacted almost all sectors of life, as well as the micro-enterprises of the city of Bukittinggi in the convection sector as one of the economic sectors affected by this pandemic. In order to survive, convection micro business actors must be able to create a development model from the strategies that have been carried out on micro business development.The main issue that the authors study in the research in this thesis is how the micro-enterprise development model in improving the economy of the City of Bukittinggi in the pandemic era and how the review from a sharia economic point of view of the strategy for the survival of micro-enterprises in improving the economy in the Covid-19 pandemic era. while the general objective to be achieved in the research is to find out the development model used by convection micro business actors so that they can survive in the midst of a pandemic from a sharia economic point of view.This research is a qualitative field research. By using primary data and secondary data. The analytical method used is a descriptive approach, namely identifying various problems faced by convection micro-enterprises and analyzing them using SWOT/TOWS (IFE and EFE) analysis. TOWS Matrix Analysis, SWOT Weight Table. then formulate strategies to overcome them. The data collection methods in this study were observation, FGD (Forum Group Discussion), interviews and documentation. The sample method uses snowball sampling.The results of the study found that the convection micro business development model during the Covid-19 pandemic in the city of Bukittinggi was based on a SWOT analysis and the strategies used were 1) utilizing e-commerce sales, 2) producing new convection products to be innovated, and 3) producing convection processed products that much needed during the Covid-19 pandemic such as masks. While from a sharia economic point of view, in general they have tried to apply sharia economic principles, but they are still not fully implemented by convection micro business actors such as honesty, responsibility and trust in payment of wages.